Defect studies on fast and thermal neutron irradiated GaN - Lorenz, K.
Single crystalline epitaxial GaN films were irradiated with fast (E > 1 MeV) or with fast and thermal neutrons. These irradiation conditions allow the separation of the effect of transmutational doping with Ge due to nuclear reactions with thermal neutrons on the damage production. High resolution X-ray diffraction showed an expansion of the c-lattice parameter after irradiation which is reversed after annealing at 1000 °C. The effect of neutron irradiation on the optical properties of GaN samples was investigated using photoluminescence and Raman spectroscopies. With above band gap excitation the PL spectra of the as-irradiated sample with fast and thermal neutrons is dominated by broad emission bands in the UV and yellow spectral range whereas no PL is observed for the fast neutron as-irradiated sample. Annealing the as-irradiated samples promotes the damage recovery and noticed changes are observed in the PL spectra. Raman scattering spectra indicate an increase of the intensity of the disorder activated phonons revealing higher lattice damage for the irradiation with fast and thermal neutrons.